A Criminological Analysis of Drug-Related Crimes Among Adolescents - Hastuti Nur Herawati; Diya Ul Akmal; Rizkatul Wahdiyah; Dinar Putri Gunawan (Perspective Humanities and Social Sciences, 2026)
The aim of this article is to review and analyze the factors that cause narcotics crime among teenagers through a criminological approach. Furthermore, the article underscores the necessity for preventive measures in combating substance abuse among adolescents. The present article employs qualitative data analysis, deriving its data from a comprehensive review of extant literature. The results of the study demonstrate that adolescence constitutes a vulnerable period with regard to the circulation and abuse of narcotics. Adolescents frequently find themselves susceptible to exploitation due to their innate curiosity and the absence of a fully developed understanding of their actions. This phenomenon places the Indonesian nation in a critical state, as adolescents are the foundation of the nation's future. A comprehensive strategy is imperative to address the plight of adolescents grappling with substance use disorders, encompassing both those who use drugs and those who engage in the illicit transportation of such substances.